EFFECT OF FREEZING DURATION AND DOUGH IMPROVER ON THE SENSORY PROPERTIES OF PARTIALLY PROOFED AND FRESHLY BAKED CROISSANTS - VAIDA MAKARAVIČIENĖ; EVALDAS JUŠKA; EGLĖ PURVANECKAITĖ (Innovare Journal of Food Sciences, 2025)
Objective: This study aimed to evaluate how freezing duration affects the sensory properties of partially proofed croissants with 2% dough improver and to determine the maximum freezing period that maintains acceptable quality. Methods: Croissants were partially proofed for 1.5 - 3 h, depending on intended storage, frozen at –23 °C for up to 15 days, then defrosted at room temperature and baked at 165 °C for 18 min. A trained panel of six assessed appearance, colour, texture, aroma, and taste using a 5-point hedonic scale. All analyses were performed in triplicate, with significant differences determined by one-way ANOVA (P < 0.05). Results: Croissants retained good sensory quality for up to 10 days of freezing, with no significant changes in appearance, colour, texture, aroma, or taste. Beyond 10 days, slight declines were observed in dough rise, crust appearance and colour, internal texture, and overall sensory scores, indicating that prolonged freezing adversely affects product quality. Conclusion: Partially proofed croissants with dough improver can be frozen for up to 10 days without significant loss of sensory quality, while longer storage may reduce appearance, texture, and overall acceptability.